PENDAMPINGAN DAN PELATIHAN TEKNIK BUDIDAYA TANAMAN HORTIKULTURA UNTUK MENINGKATKAN PRODUKTIVITAS PERTANIAN DI KELURAHAN CIKERAY KECAMATAN CIBEBER, KOTA CILEGON - Surachman, Surachman; Nurasiah, Iis; Ibrohim, Ibrohim (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service activity aims to improve horticultural agricultural productivity in Kelurahan Cikeray, Kecamatan Cibeber, Kota Cilegon through guidance and training on environmentally friendly cultivation techniques. The training method employs a participatory approach combining brief theoretical sessions and hands-on practice in the field. Participants included active local farmers and agricultural extension workers. The results showed significant improvement in participants’ knowledge, high adoption rates of new techniques such as organic fertilizer use and drip irrigation, and the formation of an active Farmer Assistance Group conducting regular meetings to share experiences and solutions. The impact of this activity is reflected in increased horticultural crop productivity, contributing positively to farmers’ welfare and local food security. This program’s success demonstrates that technology transfer focused on local needs and conditions can sustainably empower farmers and improve agricultural production quality